The Analysis of Sloshing Reduction System Performance through Implementation of Tune Mass Damper (TMD) Technology into the Fully Filled Downscaled Flexitank - Ahmad Mohsin, Muhammad Hafizuddin; Yong Tze Mi, (Progress in Engineering Application and Technology, 2024)
This bachelor final year project is about the study of Tuned mass Damper (TMD) trial application into the liquid sloshing structure of Downscaled Flexitank (DF) with flexible wall and fully filled condition, a structure of supporting plate that is constructed by ellipsoid curve and undulated layer is used as the TMD support system. This fabrication processes are included prototype development and TMD design on the flexitank. The experimental testing method used by following the standard of ASTM D999-2015, Method A2. A corrugated shipping container in 8 times downscaled is designed by previous student and fabricated by MY Flexitank Sdn Bhd is utilized. The flexitank is made of Linear-Low Density Polyethylene (LLDPE) with thickness 5-mil and specific size. The dimension of flexitank and shipping container are downscaled 8 times. The data type is gained based on the force sensors used which are Force Sensing Resistor with 6 units are placed on the CTU downscaled shipping container platform and connected to the Arduino Uno R3 and Arduino Integrated Developer Environment (IDE). The result and discussion describe about the comparison of sloshing force on different speed and condition against the variation of TMD mass ratio from 1% until 5% subjected to the flexitank loaded mass.